2024
DOI: 10.1159/000536145
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Autopsy Findings in Patients with Pyoderma Gangrenosum: A Multi-Institutional Series

Hadir Shakshouk,
Mallory deCampos-Stairiker,
Shannon Kody
et al.

Abstract: Introduction: Pyoderma gangrenosum (PG) is a rare ulcerative skin condition with an increased risk of mortality compared to the general population. The causes of this increased risk are not well understood. Misdiagnosis is common in pyoderma gangrenosum, and many studies are limited by the inclusion of misdiagnosed cases. The goal of this study is to review autopsy findings, identify causes of death, and identify factors that may worsen outcomes among deceased patients confirmed to have PG. Methods: Data was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…While those with cancer are inherently at increased risk for infection, ND may independently further increase the risk given that many patients have open wounds and are treated with systemic corticosteroids. Notably, a recent case series suggested that pyoderma gangrenosum may modify the time to mortality among those with inflammatory bowel disease and rheumatoid arthritis, although the study was unable to comment on hematologic malignancy [17].…”
Section: Discussionmentioning
confidence: 92%
“…While those with cancer are inherently at increased risk for infection, ND may independently further increase the risk given that many patients have open wounds and are treated with systemic corticosteroids. Notably, a recent case series suggested that pyoderma gangrenosum may modify the time to mortality among those with inflammatory bowel disease and rheumatoid arthritis, although the study was unable to comment on hematologic malignancy [17].…”
Section: Discussionmentioning
confidence: 92%